World Economic Outlook, October 1988. (World Economic Outlook; World Economic Outlook ;, 1988)
This paper highlights that the performance of the world economy in the first half of 1988 has been considerably more satisfactory than was expected in the wake of the sharp stock market decline in October 1987. Output in industrial countries has grown strongly, world trade has been robust, and inflation appears to have remained under control. Moreover, the shifts in real trade flows induced by earlier exchange rate movements are at last beginning to have a visible effect on the payments imbalances of the three largest countries.